Fraquezas materiais nos controles internos das empresas brasileiras emissoras de American Depositary Receipts - Titton Junior, Camila (2018)
In the face of the Brazilian political-economic oscillations, investment in the consolidated North American stock market became quite attractive. For a Brazilian company to trade its securities in this market, it must issue American Depositary Receipts (ADRs). The purpose of this study was to present the material weaknesses of internal controls evidenced by Brazilian companies that issue ADRs in the period from 2014 to 2016. A descriptive research was conducted through documentary analysis and qualitative approach of the data contained in Form 20-F companies. The results show that of the 26 companies analyzed, 9 presented material weaknesses in their internal controls. On total, 48 material weaknesses were reported, mostly corresponding to the Electricity sector. The categories with the highest percentage of material weaknesses were Accounting Policies and Senior Management. The component and objective of COSO most affected were, respectively, Control Activities and Operational. PriceWaterhouseCoopers was the audit firm that most identified material weaknesses and Deloitte Touche Tohmatsu rated the largest number of companies. Companies that have material weaknesses tend to be smaller, more complex, less profitable, audited more often by a large audit firm, and more likely in rapidly growing or restructured companies. Disclosure of information about material weaknesses results in negative stock price returns, however, the market reaction is somewhat less negative when the company hires a Big Four audit firm.